A reading of safeguarding tools and strategies, between planning and observation: Case of study: the casbah of Dellys, the casbah of Algiers, the Douirette of Blida - Chamma, Amel (Journal of Architecture and environment of child, 2021)
Algeria manifests itself with an important richness in terms of built heritage, classified or not classified. This observation led us to question the strategies available to safeguard this real estate which are deteriorating more and more. This research work will be based on in situ investigation, photography being the basic material on which the literature search is articulated in order to understand the strategies and the vision that should be supported by the implementation of the backup plans withdrawn by an analysis of three study cases classified at the local level ‘Douirette of Blida’, national ‘casbah of Dellys’ and global ‘casbah of Algiers’. Our research has revealed that undeniable efforts have been made at the theoretical and strategic level in the form of safeguard plans such as PPSMVSS, the institution of a national agency of safeguarded sectors ANSS, collaboration with foreign groups ‘Montada’ and another initiative at the regional level, but its mode of application makes the mistake, and this is due to the miscoordination between the different sectors of task management, and the implementation thus the poorly treated economic data, despite the fact that the studies for these three study cases are distinguished by an important hierarchy, despite their status, the execution operations are almost the same.